Use of Vectors to Explore Visual Meaning Making - Alzahrani, Bashayir; Alhuthali, Mohammed (International Journal of Language and Literary Studies, 2023)
The role of women in Saudi society has regularly attracted attention. To many non-Saudis the historic restrictions are seen as evidence of deep and fundamental discrimination and the complexities of how restrictions and freedoms interact overlooked. Since 2017, there have been a series of major reforms to the male guardianship system and this has opened up public spaces for women as well as ending the emblematic ban on women driving. However, in turn, this has seen contested interpretations with criticisms of the limited nature of the reforms contrasted with those who see them as a major and significant step. This study looks at a series of images of women in public spaces in Saudi Arabia both before and after the recent reforms. The importance of vectors within the image as a means to combine different semiotic modes is the main research tool for understanding intersemiosis. This also allows a study of whether the represented actors are seeking to directly engage with the external viewer or if their focus is bounded by the image. This stresses the importance of intersemiosis in understanding the individual semiotic modes in an image. However, it also stresses that intersemiosis, in itself, cannot explain the wider process of resemiosis.